Pendidikan berbasis Moderasi Beragama Dalam Al-Qur’an - Muhammad Syawal Karo Karo, Syawal; Kurniawan, Pandi; Khairani, Dede; Diva Aldair Siregar, Muhammad; Al Farabi, Mohammad (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2024)
The Quran is the Holy Book of the Muslims, which is relevant to all ages and places. Religious moderation is a theory that contains the notions of moderation, fairness and centrality in every aspect of life in this world. (Pembentukan Syariat). While the term religious moderation is always described in the Qur'an in a large set of different types of character, among others character Honesty, openness of mind, love, and luwes character, which are mutually integrated, holistic and universal, all inseparable, mutually reinforcing and beneficial. The four suras in the Qur'an are Q, S Al Baqarah 143, Q.S Al Ankabut verses 46, Q.s Al An'am verses 108 and Q. S Al Mumthah verses 8. In this case also appears the Asbabun Nuzul, Tafsir Ayat and the meaning contained in the Quran about Religious Moderation. The authors used the Libray Research method, which is to use sources of reading through books, journals, and interpretations to study and analyze this research. In addition, the authors also used the method of analytical interpretation.